Safety and efficacy of crizotinib in patients with advanced or metastatic ROS1-rearranged lung cancer (EUCROSS): a European phase II clinical trial - Michels, Sebastian; Bischoff, Helge (Journal of thoracic oncology, 2019)
INTRODUCTION: ROS1 rearrangements are found in 1% of lung cancer patients. Therapeutic efficacy of crizotinib in this subset has been shown in early phase trials in the United States and East Asia. Here we present data on efficacy and safety of a prospective phase II trial evaluating crizotinib in European ROS1-positive patients (EUCROSS). - PATIENTS AND METHODS: The trial was a multicenter, single-arm phase II trial (Clinicaltrial.gov identifier: NCT02183870). Key eligibility criteria included patients who were 18 years of age or older with advanced/metastatic lung cancer and centrally confirmed ROS1-rearranged lung cancer (fluorescence-in situ hybridization). Treatment included 250 mg crizotinib twice daily. The primary endpoint was investigator-assessed objective response rate (ORR) (Response Evaluation Criteria in Solid Tumors, version 1.1). Key secondary endpoints were progression-free survival (PFS), overall survival, efficacy by independent radiologic review, safety, health-related quality of life, and molecular characterization of tumor tissue. - RESULTS: Thirty-four patients received treatment. Four patients were excluded from efficacy analysis. Investigator ORR was 70% (95% confidence interval [CI]: 51-85; 21 of 30 patients) and median PFS was 20.0 months (95% CI: 10.1-not reached). Two patients with ROS1 wild-type sequences assessed by DNA sequencing had progression as best response. CD74-ROS1-positive patients had a trend towards a higher ORR and longer median PFS. TP53-co-mutant patients had a significantly shorter median PFS than wild-type patients (7.0 months, 95% CI: 1.7-20.0 versus 24.1 months, 95% CI: 10.1-not reached; p = 0.022). Treatment-related adverse events were documented in 33 of 34 patients (97%). - CONCLUSIONS: Crizotinib is highly effective and safe in patients with ROS1-rearranged lung cancer. ROS1-/TP53-co-aberrant patients had a significantly worse outcome compared to TP53 wild-type patients.
Gesehen am 01.08.2019